Salvaguarda e valorização do edificado habitacional da cidade histórica. Metodologia de intervenção no sistema construtivo da casa burguesa do Porto. - Joaquim José Lopes Teixeira (2014)
The ordinary buildings of the city of Porto, mostly represented by the bourgeois house, are heritage assets at risk of disappearing, not only as a result of its advanced state of disrepair due to decades of neglect, but also for the risk of misuse of this irreplaceable resource. Although some of this heritage is located in a listed area, the majority of these ordinary buildings are scattered throughout the settled city, without any protection, thus at the mercy of real estate speculation and callous actions that have gradually dilapidated its features through reconstruction interventions. The intervention in aged buildings is a highly complex operation that involves the mobilization of various resources, easily justifiable for monuments restoration but difficult to pull together for the ordinary built fabric. It is therefore of paramount importance to find ways of intervening on the constructive system of the ordinary building to ensure the protection of its heritage values, through the recovering of traditional materials and techniques, while responding to contemporary housing requirements, such as safety, comfort, hygiene or functionality, amongst others. This study develops the characterization and classification of the constructive system of the bourgeois house in Porto, which allowed for the design of a constructive model, fundamental to the development of the proposed methodology for intervention. The design of this methodology draws its principles and criteria for intervention from the history of theories of heritage conservation (as far back as Valadier's and Stern's interventions to international documents and charters). Similarly, the definition of the urban dimension strategy refers to the main experiments of national and international urban intervention, in particular to the work of CRUARB (Commissariat for the Ribeira and Barredo Areas Urban Renewal). The demeanour of the principles of a more sustainable society is also here pursued with reference to sustainable architecture practice. The proposed methodology is heavily reliant on design and it aims to assist the undertaking of surveys (i.e. geometric, constructive, elements of value, changes and anomalies), helping to overcome many constraints which are typical of this preliminary stage and thus speeding up the definition of diagnosis. Based on the ten components that embody the constructive model, the proposed solutions address the likely main themes of action, covering from the simple maintenance to the rehabilitation with the addition of new elements. As such, and following the principles underlying the practices enshrined in international documents, the intervention solutions are divided in five main actions: selective demolition (if applicable); repair of damages; structural strengthening; improvement of performance; and addition of new elements. Finally, the maintenance actions corresponding to the post intervention are also addressed, as they also play a fundamental role in the safeguarding of the existing heritage.